Perancangan Data Warehouse untuk Analisis Penjualan Ritel Elektronik Berbasis Business Intelligence - Reno Naufal Maulidyan; M. Muharrom Al Haromainy (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study proposes a data warehouse design based on a star schema to support electronic retail sales analysis using PostgreSQL, Pentaho Data Integration, and Tableau. The objective is to transform heterogeneous transactional data into a structured analytical environment that can improve business intelligence capability. The research method includes data ingestion into a relational database, staging area construction, ETL-based cleansing and standardization, dimensional modeling, datamart development, and interactive dashboard visualization. The resulting architecture enables multidimensional analysis across time, product, region, sales channel, payment method, and customer type. The findings indicate that the proposed system improves data consistency, analytical efficiency, and decision-support capability, making it suitable as a foundation for retail performance monitoring and strategic planning.